Analisis Kesalahan Pada Spanduk Kantin Bina Insan Islamic School (Kajian Morfologi) - Suci Wulan; Puspa Indah Utami; Dessy Wardiah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to determine language errors in the field of morphology in food banner media. This research is qualitative research with content analysis methods. The data used in this research are sentences containing linguistic errors at the morphological level on food banners in the Bina Insan Islamic School Canteen. The data source used is the food banner in the Bina Insan Islamic School Canteen. Data collection techniques use reading and note-taking techniques. The data analysis technique is using data reduction techniques, data presentation and drawing conclusions. Based on the data found and analyzed, it can be concluded that the writing on food banners often contains language errors at the morphological level related to word writing. This research examines five data related to errors in adding phonemes, subtracting phonemes, errors in standard and non-standard words, and word abbreviations.